2021
DOI: 10.5114/fmpcr.2021.108201
|View full text |Cite
|
Sign up to set email alerts
|

INKOLA based on Orem’s Self-Care Model and its effectiveness on the quality of life and HbA1C in children with type 1 diabetes mellitus

Abstract: Background. The quality of life for children with diabetes type 1 is determined by the ability of parents to care for their children independently. The INKOLA model was developed from the Dorothea Orem self-care deficit model, which emphasized educational support for patients' self-care and independence.Objectives. This study aims to determine the effectiveness of the INKOLA model on the QoL and HbA 1C of T1DM children. Material and methods. Our quasi-experimental study with a control group was carried out on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Similarly, the QoL and anxiety of cancer patients did not differ significantly after an intervention based on SCDNT and routine care (Grant, 1990; Jamshidzahe Dejange et al., 2018; Wengstrom et al., 1999). In the same vein, SCDNT‐based nursing was not effective in the QoL of patients with T2DM and CKD, self‐efficacy of patients with CKD and COPD, anxiety and stress of patients with MS, and depression of women with endometriosis (Aghakhani et al., 2012; Bal Ozkaptan & Kapucu, 2016; Farshi et al., 2020; Habibzade et al., 2012; Rahimi et al., 2014; Rumahorbo et al., 2021; Shahdadi et al., 2017a; Shahdadi et al., 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the QoL and anxiety of cancer patients did not differ significantly after an intervention based on SCDNT and routine care (Grant, 1990; Jamshidzahe Dejange et al., 2018; Wengstrom et al., 1999). In the same vein, SCDNT‐based nursing was not effective in the QoL of patients with T2DM and CKD, self‐efficacy of patients with CKD and COPD, anxiety and stress of patients with MS, and depression of women with endometriosis (Aghakhani et al., 2012; Bal Ozkaptan & Kapucu, 2016; Farshi et al., 2020; Habibzade et al., 2012; Rahimi et al., 2014; Rumahorbo et al., 2021; Shahdadi et al., 2017a; Shahdadi et al., 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Ghanbari & Kazemnezhad revealed that 60% of patients exhibited inadequate self-care quality [31]. Another investigation highlighted the efficacy of the INKOLA model, based on Orem's self-care framework, in enhancing quality of life and managing Hemoglobin A 1 C levels for individuals with type 1 diabetes [21]. Additionally, a study by Hemati et al, underscored the contributory role of Orem's self-care model in augmenting the quality of life among adolescents with asthma, suggesting its potential use as a health intervention to enhance asthma control and patient adherence [22].…”
Section: │ Discussionmentioning
confidence: 99%
“…However, reduced self-care activities among diabetic patients can exacerbate disease complications [20]. A study by Hotma et al, concluded that an educational program rooted in the Orem's model can enhance children's quality of life and effectively manage hemoglobin levels [21]. Similarly, another study by Hemati et al, in Iran demonstrated that applying the self-care model for asthma negatively impacted the quality of life among adolescents with chronic asthma, yet proved to be a beneficial approach in bolstering patient control and adherence [22].…”
Section: │ Introductionmentioning
confidence: 99%
“…There are several concepts, models or theories that are used in the management of diabetes mellitus patients, both on an individual basis and involving families and health workers with the aim of increasing the ability and compliance of diabetes mellitus patients in self-management. Self-management as part of self-care, both are based on the philosophy that individuals are responsible for their own health (Gumbs, 2020;Rumahboro, Karjatin and Hamzah, 2021). In accordance with the principles in nursing philosophy, the central core of nursing is the nurse-patient relationship (Skinner et al, 2003;Kalra, Baruah and Kalra, 2017).…”
Section: Introductionmentioning
confidence: 99%